Optimal PID tuning based on slope variation approach for position control of radio telescope - Mohamad Zaber, Nursaida (2016)
Radio telescope is an astronomical instrument used to study radio astronomy activities including observing the celestial activities such as sun, galaxies, pulsars, stars, monitor the submillimeter wavelength and many more. Radio waves received are very weak and of low intensity. Due to this, the signals are easily distracted by interference. To resolve this, antenna dish has been increased in size which gives a larger collecting areas and increased its operating frequency. However, another difficulty arises and create challenges in controlling and positioning the radio telescope. On top of that, the antenna is also exposed to disturbances namely wind disturbance that makes the control process even worse. In view of that, with the aim to have an accurate position output, it is essential to employ a precise and robust controller. This research utilised a PID controller for position control of the radio telescope. However, PID faces big challenges in determining its parameters values. It suffers unsatisfactory performance such as time consuming, tedious work, lack of precision and robustness. Thus, an optimal approach is proposed to obtain the parameters by using slope variation method. Radio telescope was modelled based on real telescope with 18-m diameter. A Ziegler Nichols (ZN) and ZN+ were executed during control process. These methods were chosen since they are one of the widely use method for tuning PID. Then the slope variation approach implemented to the radio telescope model. The control methods were run in speed loop followed by position loop. Performance of the proposed approach was compared with ZN and ZN+ methods. The results showed that the slope variation approach provide promising results in terms of precision and percentage of overshoot with 0.001° position accuracy and zero overshoot. On the other hand, ZN+ method obtained only 0.034° of position accuracy and 5% overshoot. Realising radio telescope continually exposed to wind gust disturbance, the wind gust was modelled together with the radio telescope model. The wind gust is designed based on the wind speed in Malaysia where it differs according to the seasons. Malaysian Meteorological Department (MET) recorded the slowest wind speed is 10 knots while the highest wind speed is 81.06 knots. Thus, the proposed controller is tested to control the radio telescope position with presence of wind gust disturbance as mentioned above values. The conducted tests showed the position accuracy employing slope variation approach reduce to 0.0012° but still in the expected range while ZN+ method 0.053°. The PID controller using slope variation approach has successfully control the position of radio telescope and meets the designed specifications. Not only that, the proposed approach also able to overcome the highest possible wind gust disturbance with small deviation and satisfactory position accuracy.